From Stockholm to Rio: Critical Reading of Global Environmental Governance - Robertua, Verdinand; Bainus, Arry (AEGIS : Journal of International Relations, 2018)
Global environmental governance is deeply undermined due to the problem of overlapping function and lack of funding. It is then important to trace the history of the construction of global environmental governance as an institution. This article would like to understand the dynamics of global environmental governance from Stockholm Conference in 1972 to Rio Conference in 1992. The changes between Stockholm Conference and Rio Conference will be analyzed using English School theory. English School theory has the potential to critically engage with the taken-for-granted norms and institutions. Pluralism and solidarism as the normative wings of English School can elaborate the key driver of global environmental governance. It is expected that this article can contribute to development of environmental studies of English School theory and the formulation of global environmental governance.Keywords: global environmental governance, English School theory, Rio Conference, Stockholm Conference, sustainable development